Perception and View of Consumers on Food Irradiation and the Radura Symbol - Valenzuela-Bascunan, X; Galotto-Lopez, M; Junqueira-Conceicao Goncalve, M; Marchan-Dinten, C (2011)
Sin Editorial Disponible